Automated Software Tool Support for Checking the Inconsistency of Requirements - Kamalrudin, Massila (2009)
Handling inconsistency in software requirements is a complicated task which has attracted the interest of many groups of researchers. Formal and semi-formal specifications often have inconsistencies in the depicted requirements that need to be managed and resolved. This is particularly challenging when refining informal to formalized requirements. We propose an automated tool with traceability and consistency checking techniques to support analysis of requirements and traceability between different representations: textual, visual, informal and formal.